Distribution of HPV types among patients with positive histological findings for cervical precancerous lesions and invasive cancer of the uterine cervix - Dimitrov, Goran; Dzikova, Elena; Dimitrov, Gligor; Tofoski, Gligor; Daneva Markova, Ana; Joksimovic, Marija; Kjajova, Ivana (Македонско лекарско друштво = Macedonian Medical Association, 2018)
Introduction. The aim of this study was to provide basic data on the prevalence of different HPV types among the female population in R. Macedonia with histologically proven cervical intraepithelial neoplasia or invasive cervical cancer, in order to better plan the vaccination program and screening for cervical cancer. Mеthods. This study retrospectively statistically (using Statistica SPSS for Windows) analyzed histological findings positive for cervical intraepithelial neoplasia or invasive cervical cancer and positive HPV genoty- ping results of564 patients who came to the University Clinic for Gynecology and Obstetrics due to an abnor- mal Pap smear test during the last year (2017). Results. HPV isolation showed the presence of human papillomavirus in78% of the total of 564 subjects. The prevalence of HPV in LSIL, HSIL, invasive squamo- cellular carcinoma of the uterine cervix and adeno- carcinoma of the uterine cervix was 69.2%, 87.2%, 97.6% and 71.4%, respectively. HR HPV types were isolated in 75%of LSIL and 96% of HSIL. Predo- minantly isolated were HPV types 16, 18, 35, 31, 33, 58, 6, 11 and 40. HPV type 16 wasthe most commonisolated genotype among all patients with 48.4%, 30.1% and 19.6% in HSIL, invasive carcinoma and LSIL, respect- tively. HPV type 18 had the highest rate in patients with invasive adenocarcinoma of the cervix (30.1%). Conclusion. Human papillomavirus types 16, 18, 35, 31, 33, 58, 6, 11 and 40were the predominant high risk types in patients with invasive cervical cancer and its precursors in the Republic of Macedonia.
Дистрибуција на ХПВ типовите меѓу пациентки со позитивни хистолошки наоди за цервикални преканцерозни лезии и инвазивен цервикален карцином
Keywords: HPV types; SIL; cervical cancer